Efficacy of Emamectin benzoate, Spinosad and Tolfenpyrad on Tuta absoluta Meyrick (Lepidoptera: Gelechiidae) infesting a tomato crop under geothermal greenhouses in Southern Tunisia - Sabrine Chouikhi; Besma Assadi; Refki Ettaib; Kaouther Lebdi Grissa; Mohamed Sadok Belkadhi (Journal of Oasis Agriculture and Sustainable Development, 2022)
The tomato leaf miner, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), is considered one of the most devastating pests of tomato crops in geothermal greenhouses. It leads to crop losses reaching 100% among farmers and major tomato exporters. In this research, three insecticides, Emamectin benzoate, Spinosad and Tolfenpyrad were evaluated for their efficacy in the control of T. absoluta larvae in heated greenhouses. These three treatments resulted in a significant reduction in the number of T. absoluta larvae compared to an untreated control. The Emamectin Benzoate, Spinosad and Tolfenpyrad used were effective in controlling this leafminer with efficacy percentages above 60% against young larvae and above 50% against old larvae.